Simple ways to succeed in academic writing - Maruf, Irma Rachmawati; Damin, Zahrul Akmal; Mohd Sofian, Fatimah Noor Rashidah; Inkeree, Hareesol Khun (Mega Press, Collaboration with UNISMA, 2022)
Writing is a means for an author to communicate himself, and the clearer his statements are, the simpler it is for readers to understand what the writer is trying to convey. However, providing a clearer picture of what one means does not provide readers with much joy. Readers want a strong 'flow of ideas', with adequate connection from one paragraph to the next. To make reading more enjoyable, an author or writer should use criticism writing in their explanation of specific difficulties mentioned in a paragraph. This book will benefit writer to develop the concept that one has in mind into writing.